The role of foreign investment in U.S. infrastructure: opportunities and challenges ahead - Petsas, Iordanis; Vidalis, Sofia M (Economics and Business Letters, 2020)
The U.S. infrastructure has been issued a grade of D+ from the American Society of Civil Engineers because of the low funding for new construction, maintenance, and repair. It is now reaching the end of its useful life and cost estimates have reached as high as $3.6-trillion. The public infrastructure investment is at 2.4% of GDP, which is half of what it was 50-years ago. The U.S. has explored new ways to finance its infrastructure because of funding uncertainty. Investments such as, pensions, foreign investments, and sovereign wealth funds, manage trillions in assets and are forecasted to grow. This paper presents an overview in infrastructure funding and identifies possible approaches in addressing long-term financial needs with foreign capital partnership.